The Coiled Viper - Abbott, Tony.; Jessell, Tim (New York : Scholastic, 2003)
Magic on Main Street?!! The border between Droon and the Upper World has been crossed. And now evil Sparr is in Eric's hometown! On a search for the Coiled Viper, he's turning the Upper World inside out. Talking frogs, flying kids, a Ninn parade down Main Street...There's Droon magic all over our world! Can Eric and his friends keep it secret?
"A Little Apple paperback."
8 9 13
Keywords: Magic -- Fiction; Secrets -- Fiction; Fantasy